Pengaruh Penambahan Pasir Terhadap Tingkat Kepadatan dan Daya Dukung Tanah Lempung Organik - Ferdian, Ferdi; Jafri, Muhammad; Iswan, Iswan (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
The problem of density level and bearing capacity of soil is one of things that really need toconsidered in the planning and construction work of a civilian building . This is because the landin question serves as a medium that holds the load or the action of a construction that is built on it. Stabilization using sand material is one way to meet the needs of the required strength . Changesin weather and temperature in the field are factors that makes the soil unstable .The type of soil is organic clay stabilized from the Gedong Pasir village, Jabung District, EastLampung District. This research was conducted by using a mixture of sand with variations mixtureof 5 %, 10 % and 15 %. After the CBR testing, Density, Atterberg Limits and Specific Gravity foreach sample.The more variations of a mixture of sand were added resulting in declining water levels that wouldmake the value of the soil carrying capacity increases, the value of density and plastic limitincreased, while the value of the liquid limit and plasticity index decrease.Keywords: sand, organic clay, bearing capacity